Ameliorating effects of two extracts of Nigella sativa in middle cerebral artery occluded rat - Mohammad Akhtar; Aliyu Muhammad Maikiyo; Razia Khanam; Mohd Mujeeb; Mohd Aqil; Abul Kalam Najmi (Wolters Kluwer Medknow Publications, 2012)
Purpose: Aqueous and hydroalcoholic extracts of Nigella sativa (400 mg/kg, orally) for 7 days were administered and evaluated for their neuroprotective effects on middle cerebral artery occluded (MCAO) rats. Materials and Methods: Cerebral ischemia was induced by middle cerebral artery occlusion for 2 h followed by reperfusion for 22 h. After 24 h of ischemia, grip strength, locomotor activity tests were performed in the surgically operated animals. After behavioral tests, animals were immediately sacrificed. Infarct volumes followed by the estimation of markers of oxidative stress in the brains were measured. Results: Locomotor activity and grip strength of animals were improved in both aqueous and hydroalcoholic extracts pretreated rats. Infarct volume was also reduced in both extracts pretreated rats as compared with MCAO rats. An elevation of thiobarbituric acid reactive substance (TBARS) and a reduction in glutathione and antioxidant enzymes, viz., superoxide dismutase (SOD) and catalase levels were observed following MCAO. Pretreatment of Nigella sativa extracts showed the reduction in TBARS, elevation in glutathione, SOD and catalase levels as compared with MCAO rats. Conclusion: The present study observed the neuroprotective effects of both the extracts of Nigella sativa in cerebral ischemia. The neuroprotective effects could be due to its antioxidant, free radical scavenging, and anti-inflammatory properties.